Respuesta ambiental en el Pacífico frente a la subducción de la dorsal asísmica de Cocos (Panamá y Costa Rica) Environmental response in the Pacific to aseismic Cocos Ridge subduction (Panama and Costa Rica) - Carlos De Gracia; Aaron O’Dea; Félix Rodríguez; Luis D’Croz (Revista de Biología Tropical, 2012)
Con el fin de evaluar el efecto de la Subducción de la Dorsal Asísmica de Cocos (DAC) durante las etapas finales de la formación del Istmo. Realizamos muestreos con bultos en afloramientos fosilíferos en las penínsulas de Burica y Nicoya. Las condiciones paleoecológicas y paleoambientales fueron reconstruidas a partir de la comparación entre la estructura de las comunidades fósiles, con las comunidades modernas dragadas de los mares de Panamá, usando análisis de componentes principales. Los resultados indican que antes del cierre del Istmo, existieron islas oceánicas y un afloramiento moderado en Burica. Posterior al cierre, el choque de la DAC provocó la elevación del fondo marino y las aguas que se encontraban a 2 300m pasaron a 40m. El afloramiento se intensificaba en mar abierto pero la dorsal había formado islas en Burica que limitaban el efecto del afloramiento en la costa. La subducción de la DAC continuó y las islas se unieron gradualmente a tierra firme y desaparecieron, permitiendo el afloramiento. Durante el Pleistoceno medio un segundo proceso de levantamiento acelerado continuó elevando el fondo marino y formó la Cordillera de Talamanca. La cordillera creó una barrera que bloqueó el paso de los vientos Alisios y originó condiciones ecológicas y optimas que permiten el crecimiento de los mejores arrecifes de coral costeros del Pacífico oriental tropical (POT) entre Panamá y Costa Rica. Environmental response in the Pacific to aseismic Cocos Ridge subduction (Panama and Costa Rica). The evolution of the marine communities along the Pacific coast of Central America, may have changed in response to the formation of the Isthmus of Panama. To evaluate the effect of the Aseismic Cocos Ridge (DAC) subduction on the marine benthic communities, we reconstructed benthic assemblages from Neogene fossiliferous formations in Burica and Nicoya peninsulas of Panama and Costa Rica. Paleoecological and paleoenvironmental conditions were reconstructed by comparing community structure from bulk fossil samples with dredge collections from modern Tropical American seas, using principal component analysis. Our results indicate that during the early Pliocene, before the closing of the Isthmus, some oceanic islands existed with moderate upwelling in the Burica region. After the closure, during the late Pliocene and early Pleistocene the collision of the DAC caused an uplift of the seafloor, where water depth of 2 300m became shallow waters of less than 40m depth. Meanwhile, upwelling intensified in the open ocean the uplift that had formed small islands in coastal areas of Burica, creating protected areas and limiting the upwelling effect that was given in open ocean. The subduction of the DAC continued until the islands were joined to the mainland and gradually disappeared, allowing the return of the upwelling. During the middle Pleistocene a second process of accelerated uplift ith speeds of 8m/1 000 years provoked again the elevation of the seafloor and later the elevation of the Talamanca Range. The new range formed a barrier that blocked the passage of the Trade winds, created new ecological conditions and optimized and allowed the growth of the best coral reefs in the coasts of the tropical Eastern Pacific (POT) between Panama and Costa Rica. Rev. Biol. Trop. 60 (2): 893-908. Epub 2012 June 01.